The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3310/hta16080
|View full text |Cite
|
Sign up to set email alerts
|

Group art therapy as an adjunctive treatment for people with schizophrenia: a randomised controlled trial (MATISSE).

Abstract: on behalf of the MATISSE project teamHow to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 71 publications
(22 reference statements)
2
76
1
Order By: Relevance
“…8 In this study, no significant improvements in either negative symptoms or any of the secondary outcomes were found in the art therapy group, relative to either the active control group or standard care. The MATISSE trial 8 was designed as a pragmatic trial with the aim of testing the impact of group art therapy delivered in current clinical practice, meaning that one specific model of therapy was not evaluated. Consequently, the type of treatment provided was not consistently applied, which has been criticised by some art therapists, who have suggested that what was evaluated is not what is routinely delivered in the UK.…”
Section: Schizophrenia and Arts Therapiescontrasting
confidence: 50%
See 3 more Smart Citations
“…8 In this study, no significant improvements in either negative symptoms or any of the secondary outcomes were found in the art therapy group, relative to either the active control group or standard care. The MATISSE trial 8 was designed as a pragmatic trial with the aim of testing the impact of group art therapy delivered in current clinical practice, meaning that one specific model of therapy was not evaluated. Consequently, the type of treatment provided was not consistently applied, which has been criticised by some art therapists, who have suggested that what was evaluated is not what is routinely delivered in the UK.…”
Section: Schizophrenia and Arts Therapiescontrasting
confidence: 50%
“…This could be considered relatively high and compares favourably with a similar trial in art therapy on this patient sample. 8 In this study, 8 participants typically reported a long duration of illness (median 11 years, IQR = 7-18), with multiple hospital admissions (median 3, IQR = 1-5) and moderate negative symptoms (PANSS negative 23.2, SD = 4.3). Overall, the participant characteristics of the sample should be considered to be both representative of the schizophrenia population in secondary care in the UK and the types of patients who would be considered appropriate for focused treatments for negative symptoms.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…• • Art therapy is included in the UK NICE clinical guideline on the treatment and management of psychosis and schizophrenia in adults (NICE, 2014), but RCT evidence is inconclusive (Crawford, 2012). • • Music therapy has a long history in schizophrenia and recent trials support its efficacy in social domains and quality of life (Grocke et al, 2009(Grocke et al, , 2014Mössler et al, 2011).…”
Section: Emerging Psychological and Psychosocial Therapiesmentioning
confidence: 99%